1996
DOI: 10.1093/oxfordjournals.aje.a008722
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Study of Air Canada Pilots: Mortality, Cancer Incidence, and Leukemia Risk

Abstract: Despite the special working environment and exposures of airline pilots, data on risk of death and cancer incidence in this occupational group are limited. The authors investigated a cohort of 2,740 Air Canada pilots who contributed 62,449 person-years of observation. All male pilots employed for at least 1 year on and since January 1, 1950, were studied. The cutoff date for outcome information was December 31, 1992. Standardized mortality ratio (SMR) and standardized incidence ratio (SIR) were used to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
118
3
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(135 citation statements)
references
References 12 publications
10
118
3
4
Order By: Relevance
“…Whereas nonmelanocytic skin cancers occur with increased risk in the occupational groups most exposed to sunlight, the highest risks for malignant melanomas are often registered in indoor occupations. For these cancer types, excess risks have been reported in studies on airline pilots conducted in Finland (79), Canada (146,147), the United States (148), Iceland (149), and Norway (150). In the Norwegian study (150), an increasing trend was observed for the standardized incidence rate with a cumulative dose for malignant melanoma.…”
Section: Criteria Used For Selecting the Studiesmentioning
confidence: 99%
“…Whereas nonmelanocytic skin cancers occur with increased risk in the occupational groups most exposed to sunlight, the highest risks for malignant melanomas are often registered in indoor occupations. For these cancer types, excess risks have been reported in studies on airline pilots conducted in Finland (79), Canada (146,147), the United States (148), Iceland (149), and Norway (150). In the Norwegian study (150), an increasing trend was observed for the standardized incidence rate with a cumulative dose for malignant melanoma.…”
Section: Criteria Used For Selecting the Studiesmentioning
confidence: 99%
“…Currently, a cohort of men working for Air Canada, however, showed a significantly increased incidence rate of acute myeloid leukemia (SIR = 4.72, 90% CI 2.05-9.31) when compared to the respective Canadian population rates [15]. There is also a case report showing that a patient with primary cerebral B-cell non-Hodgkin's lymphoma lost circadian control of sleep [16].…”
Section: Clock-cancer Connection: Epidemiological Evidencementioning
confidence: 99%
“…For example, rotating shift workers had a higher risk of prostate cancer as compared with only day-or only night-shift workers. 6,7 In addition, male airline pilots had an excess risk of prostate cancer [8][9][10] that increased with the increasing number of flight hours. 10 Although compelling, these data represent indirect associations between circadian rhythms and prostate cancer; no underlying molecular mechanism thus far has been identified.…”
Section: Introductionmentioning
confidence: 99%